Fault Detection in Synchronous Reluctance Machines - TELHIG, El Walid; AD, Boubaker; MAAMRI, Nadhir; HAMMI, Fathi (Echahid Hama Lakhdar University of Eloued, 2023)
"Key words : Synchronous Reluctance machines (SynRM) , diagnosis , Fourier Transform (FFT ) , Stator Currents , Extended Park Vector Approach , Power active and reactive , Signal Based Approaches." "في العقد الماضي ، ازداد الاتجاه نحو كفاءة أعلى وآلات كهربائية ذات كثافة عزم دوران أعلى بدون مغناطيس دائم للقطاع الصناعي بسرعة ، من بين هذه الآلات ، نميز المحرك المتزامن ذو الممانعة الذي يتميز بالعديد من المزايا مقارنة بالأنواع الأخرى من المحركات ، بما في ذلك الكفاءة العالية والتكلفة المنخفضة والموثوقية وانخفاض في الضوضاء ومتطلبات صيانة اقل . يمكن للمحرك المتزامن التعرض لأي خلل في أي وقت و بسبب ذلك خسائر كثيرة لذا ف ٍان عملية تشخيص العيوب قبل ان تتحول الى عطب في وقت مبكر أصبح أمرا ضروريا. علاوة على ذلك ، في مجال التشخيص والمراقبة للأضرار ، هناك العديد من الطرق للكشف عن الأضرار في الآلات المتزامنة و من بين هذه الطرق : طريقة تحليل الاشارة بواسطة تحويل فورييه. الغرض من هذا العمل هو المساهمة في التشخيص والمراقبة لاكتشاف الأخطاء التي تتعرض لها هذه الماكينة الكهربائية. لذا حاولنا في هذه الدراسة تشخيص عيب الماس الكهربائي لكل من تيارات الجزء الثابت و طريقة شعاع بارك و نهج القوة النشطة والمتفاعلة بطريقة تحليل الاشارة من اجل الوصول الى كشف العيب بأكثر دقة"
مذكرة ماستر الكتروميكانيكdes thèses électromécanique
Keywords: "In the past decade, the trend towards higher efficiency and higher torque density electric machines without permanent magnets for the industrial sector has increased rapidly, among these machines we distinguish synchronous Reluctance machines which have many advantages over other types of motors, including high efficiency and low cost , reliability, low noise and low maintenance requirements. The latter can be exposed to any defect at any time, and this causes many losses, so the process of diagnosing defects before they turn into damage at an early stage has become necessary. Moreover, in the field of diagnosis and monitoring of damages, there are many methods for detecting faults in synchronous machines and among these methods: The method of signal analysis by Fourier transform. The purpose of this work is to contribute to the diagnosis and monitoring to detect faults to which this electrical machine is exposed. Therefore, in this study, we tried to diagnose the electrical short circuit defect for each of the stator currents, the Park vector approach, and the active and reactive force approach using the signal analysis method in order to reach the defect detection more accurately . "; "لكلمات المفتاحية : المحرك المتزامن ذو الممانعة ، تشخيص ، تحويلات فورييه ، طريقة تحليل الاشارة ، نهج القوة النشطة والمتفاعلة، نهج متجه بارك، تيارات الجزء الثابت"